Music for ages 0 to 3 years. (Journal of Parents and Teachers, 2025)
The article consists of two sections about songs used with preschool students. Additionally, these songs are accompanied by content, objectives, resources, and activities that serve as guidelines for implementation.
Keywords: music and education; music; children; early childhood; guidelines